(untitled) (Bangladesh Journal of Pharmacology, 2014)
Antimicrobial activity of methanolic extracts of plants was screened by disc diffusion assay against four bacteria and four fungal cultures. Streptomycin (10 ?g/disc) and nystatin (10 ?g/disc) are used as standards for bacteria and fungi respectively. Minimum inhibitory concentration (MIC) of the extracts was evaluated through micro broth dilution method. The antimicrobial potency of plant extracts was assessed by their zone of inhibition and activity index values. Total activity of extracts was evaluated to quantitatively compare the activity of two plants. Methanolic extract of Cleome gynandra showed maximum antibacterial activity against Staphylococcus aureus (IZ- 22 ± 0.22 mm, AI-0.917, MIC- 0.039 mg/mL, MBC- 0.039 mg/mL). Maximum antifungal potential was shown by C. chelidonii against Candida albicans (IZ- 25 ± 0.92 mm, AI-1.000, MIC- 0.039 mg/mL, MFC- 0.039 mg/mL). Both the extracts exhibited good antimicrobial activity with low range of MIC.